Color perception differentiates Alzheimer's Disease (AD) from Vascular Dementia (VaD) patients. (22nd March 2017) - Arnaoutoglou, N. A.; Arnaoutoglou, M.; Nemtsas, P.; Costa, V.; Baloyannis, S. J.; Ebmeier, K. P.
ABSTRACT: Background: Alzheimer's Disease (AD) and Vascular Dementia (VaD) are the most common causes of dementia in older people. Both diseases appear to have similar clinical symptoms, such as deficits in attention and executive function, but specific cognitive domains are affected. Current cohort studies have shown a close relationship between αβ deposits and age-related macular degeneration (Johnson et al ., 2002 ; Ratnayaka et al ., 2015 ). Additionally, a close link between the thinning of the retinal nerve fiber (RNFL) and AD patients has been described, while it has been proposed that AD patients suffer from a non-specific type of color blindness (Pache et al ., 2003 ). Methods: Our study included 103 individuals divided into three groups: A healthy control group ( n = 35), AD ( n = 32) according to DSM-IV-TR, NINCDS-ADRDA criteria, and VaD ( n = 36) based on ΝΙΝDS-AIREN, as well as Magnetic Resonance Imaging (MRI) results. The severity of patient's cognitive impairment, was measured with the Mini-Mental State Examination (MMSE) and was classified according to the Reisberg global deterioration scale (GDS). Visual perception was examined using the Ishihara plates: "Ishihara Color Vision Test - 38 Plate." Results: The three groups were not statistically different for demographic data (age, gender, and education). The Ishihara color blindness test has a sensitivity of 80.6% and a specificity of 87.5% to discriminate AD and VaD patients when an optimal (32.5) cut-off value of performance is used. Conclusions: Ishihara Color Vision Test - 38 Plate is a promising potential method as an easy and not time-consuming screening test for the differential diagnosis of dementia between AD and VaD.